Gas Permeation Properties of Asymmetric Polyimide Membranes Made by Ion–beam Irradiation - Sannomiya, A.; Iwase, M.; Nagaoka, S.; Suzuki, Y.; Iwaki, M.; Kawakami, H. (Journal of Applied Membrane Science & Technology, 2017)
In this study, the gas permeance and selectivity of the asymmetric polyimide membrane with skin layer carbonized by He ions irradiation were measured using a high vacuum apparatus with a Baratron absolute pressure gauge at 76 cmHg and 35°C. Particutarly, we focused on the effects of the depth profile of the energy loss for the irradiating He ions in the skin layer on the gas permeation properties of the asymmetric membranes. Irradiation depth is gauged through the energy loss profile of the irradiating ions. The nature of the carbonised layer was investigated using AFM and ATR–FTIR. We demonstrated that the PO2 of the He+–irradiated membranes increased with the skin layer thickness and that the depth of the irradiating ions in the skin layer had a significant influence on the gas permeability and selectivity of the asymmetric membrane.